The relationship between audit committee and audit quality: Evidence from Nigeria - Bashir, Olagunju Olasunkanmi (2016)
The purpose of this research is to examine the relationship between non-executive directors, financial expertise of non-executive director, represent the audit committee and audit quality represent the (Big Four and non Big Four). The sample of the study is non-financial sectors in Nigerian Stock Exchange. Hence, the archival data from the annual reports were used. The model by Lawrence, Minutti -Meza, Zhang (2011) was modified to measure the audit quality as proxy for Big Four and non-Big Four. The result indicates that there was negative relationship between non-executive directors audit committee member and audit quality. This implies that larger number of non-executive directors audit committee member do not have any improvements over the audit quality. Second finding shows that there was a positive insignificant relationship exist between the financial expertise of non-executive directors audit committee and audit quality. This denotes that, having financial expertise of non-executive directors in audit committee does not improve or add to higher audit quality. This findings provide evidence on the effect of audit committee on the level of audit quality (Big Four versus Non Big Four).